Complexity of Conflict for Islamic Educational Management Student; Humanistic Approach as a Solution - Defi, Wahyu Fitrina; Gistituati, Nurhizrah (Jawda: Journal of Islamic Education Management, 2023)
The realm of Islamic educational management is not immune to conflicts, which can arise from various sources such as differing ideologies, cultural disparities, or administrative challenges. This study delves into the multifaceted dimensions of conflicts faced by Islamic educational management students. By employing a humanistic approach, this research seeks to unravel the intricate layers of conflicts within the context of Islamic education and offers innovative solutions to mitigate their adverse effects. Drawing from theories rooted in humanism, the study explores the psychological and sociocultural aspects of conflict resolution, emphasizing empathy, understanding, and effective communication. Through in-depth qualitative analysis and case studies, the research provides valuable insights into the root causes of conflicts, enabling Islamic educational management students to cultivate a harmonious learning environment. This study not only contributes to the academic discourse but also equips future leaders in Islamic education with practical strategies to navigate conflicts, fostering a conducive atmosphere for holistic learning and personal growth.